Characterization of eight terpenoids from tissue cultures of the Chinese herbal plant, Tripterygium wilfordii, by high‐performance liquid chromatography coupled with electrospray ionization tandem mass spectrometry. (21st February 2014) - Su, Ping; Cheng, Qiqing; Wang, Xiujuan; Cheng, Xiaoqing; Zhang, Meng; Tong, Yuru; Li, Fei; Gao, Wei; Huang, Luqi
ABSTRACT In this study, a reliable method for analysis and identification of eight terpenoids in tissue cultures of Tripterygium wilfordii has been established using high‐performance liquid chromatography coupled with electrospray ionization tandem mass spectrometry (HPLC‐ESI‐MS). Our study indicated that sterile seedlings, callus cultures and cell‐suspension cultures can rapidly increase the amount of biological materials. HPLC‐ESI‐MS was used to identify terpenoids from the extracts of these tissue cultures. Triptolide, triptophenolide, celastrol and wilforlide A were unambiguously determined by comparing the retention times, UV spectral data, and mass fragmentation behaviors with those of the reference compounds. Another four compounds were tentatively identified as triptonoterpenol, triptonoterpene, 22β‐hydroxy‐3‐oxoolean‐12‐en‐29‐oic acid and wilforlide B, based on their UV and mass spectrometry spectra. The quantitative analysis showed that all three materials contain triptolide, triptophenolide, celastrol, wilforlide A, and the contents of the four compounds in the cell‐suspension cultures were 53.1, 240, 129 and 964 µg/g, respectively, which were at least 2.0‐fold higher than these in the sterile seedlings and callus cultures. Considering the known pharmacological activity of triptolide and celastrol, we recommend the cell‐suspension cultures as biological materials for future studies, such as clinical and toxicological studies. The developed method was validated by the evaluation of its precision, linearity, detection limits and recovery, and it was successfully used to identify and quantify the terpenoids in the tissue cultures. Copyright © 2014 John Wiley & Sons, Ltd.